Survey of Utilization and Rationale for Handover-Mouth Technique in Under Graduate Dental Students - Periasamy, Yashila; Ravindran, Vignesh; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
When a young child displays highly disruptive, tantrum like behavior in the dental office, the practitioner needs techniques for managing the child in a quick, effective, and positive manner. A variety of relevant behavior management techniques which meet this need have been described in the literature is hand over mouth technique. The hand-over-the-mouth technique (HOME) has been proposed as a behavior management tool for communicative, but defiant children. The restraint technique sought to establish a line of communication and clear under- standing of expected behaviors from the child patient. The aim of the study was to evaluate the utilization and rationale for hand over mouth technique in undergraduate dental students. This study considered 200 undergraduate dental students studying in Saveetha dental college. They were questioned about utilization and rationale for hand over mouth technique. Collected data were statistically analyzed and results were noted. Based on the result of this survey, it appears that the level of utilization and rationale of HOME technique among the respondents is good. Therefore, additional resources and training are needed to help the undergraduate dental students to deal with such uncontrollable child.